Tianwang Buxin Granules Influence the Intestinal Flora in Perimenopausal Insomnia - Xiqian Yang (Hindawi Limited, 2021)
Study Objectives. To study the relationship between perimenopausal insomnia (PI) and intestinal flora and the potential mechanism of Tianwang Buxin granules (TWBXG) in exerting its clinical efficacy. Methods. The subjects included 13 PI patients from the Hubei Provincial Hospital of TCM, Hubei University of TCM, and Wuhan Traditional Chinese Medicine Hospital, and the corresponding noninsomniac spouses of the patients were selected as controls. TWBXG was continuously administered for 4 weeks. The feces of PI patients and their noninsomniac spouses before and after treatment with TWBXG were collected. The intestinal flora composition of each group was detected by metagenomic sequencing, and the efficacy of TWBXG was evaluated by the PSQI scale. Results. Compared with the control group, the model group showed an increase in the abundance of Roseburia faecis, Ruminococcus, Prevotella copri, Fusicatenibacter saccharivorans, and Blautia obeum, while those of Bacteroides, fecal Bacteroidetes, and Faecalibacterium prausnitzii were decreased. Compared with pretreatment, the PSQI score was significantly reduced (P<0.05), the abundance of Bacteroides, fecal Bacteroidetes, and Faecalibacterium prausnitzii increased, and that of Roseburia faecis, Ruminococcus, Prevotella copri, Fusicatenibacter saccharivorans, and Blautia obeum decreased after treatment. However, there was still a certain gap in the abundance of related flora in the treatment group compared with the control. Conclusion. PI is associated with disturbances in the intestinal flora and is mainly related to the disorders of Roseburia faecis, Ruminococcus, Prevotella copri, Fusicatenibacter saccharivorans, Blautia obeum, Bacteroides, fecal Bacteroidetes, and Faecalibacterium prausnitzii. TWBXG can effectively treat PI, and its effect may be achieved by regulating the disordered intestinal flora. Clinical Trials. The study was registered in the Chinese clinical trial registry and approved by the World Health Organization clinical trial registration platform (Effects of the modified Tianwang Buxin granule and modified Tianwang Buxin decoction pieces on insomnia: a randomized, controlled trial, ChiCTR-IPR-17011549).